Correlation between Apparent Diffusion Coefficient Values of the Renal Parenchyma and Estimated Glomerular Filtration Rates on 3-T Diffusion-Weighted Echo-Planar Magnetic Resonance Imaging - Shanigarn Thiravit (2020)
© Wolters Kluwer Health, Inc. All rights reserved. To evaluate the relationship between the apparent diffusion coefficient (ADC) values of renal parenchyma and estimated glomerular filtration rates (eGFR). Methods Data on 216 patients examined by 3-T magnetic resonance imaging for various reasons were retrospectively collected. Results There was a significant linear correlation between the ADC values and eGFRs (r = 0.254, P < 0.001). The ADC values in patients with an eGFR of less than 60 mL/min per 1.73 m were significantly lower than those with an eGFR of 60 mL/min per 1.73 m or greater. The mean ADC value of patients with grouped stage 2 disease was significantly higher than those with grouped stage 3 of chronic kidney disease (P < 0.01). Conclusions The ADC value of renal parenchyma may be a promising marker for the determination of patients with normal to mild reduction in renal function (eGFR ≥60 mL/min per 1.73 m) versus those with a moderate to severe reduction in renal function (eGFR <60 mL/min per 1.73 m).